Penggunaan Kartu Peta dalam Peningkatan Motivasi dan Hasil Belajar IPS - Dewi Nur Hidayati; Salamah Salamah (UM Purwokerto Press, 2022)
Social studies learning with broad material tends to be boring. The use of map cards is expected to increase motivation and social studies learning outcomes. This study aims to determine the increase in motivation and social studies learning outcomes in fourth grade students at SDN Ketangi. This research is a classroom action research, data collected through tests and observations. The subjects of this study were elementary school students grade IV SDN Ketangi as many as 22 students. The research instrument was a test sheet and an observation sheet. The results showed that the use of map cards increased students' learning motivation in participating in social studies lessons, it was seen that the high category was achieved by 20 students (90%) and the medium category was only 2 students (10%). The average student motivation in social studies learning reached 82%. Learning outcomes or student achievement have increased from the average class 53 to 80.